A) First, use the "completing the square" process to write this equation in the form \( (x+D)^{2}=E \) and enter your results below. \( x^{2}-16 x+63=0 \) is equivalent to: Preview left side of eqn: B) Solve your equation and enter your answers below as a list of numbers, separated with a comma where necessary. Answer(s):
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To complete the square for the equation \( x^{2} - 16x + 63 = 0 \), first, we move the constant to the other side: \( x^{2} - 16x = -63 \). Next, take half of the coefficient of \( x \), square it, and add it to both sides. Half of \(-16\) is \(-8\), and squaring it gives \(64\): \( x^{2} - 16x + 64 = 1 \). Now, we can write the left side as a complete square: \( (x - 8)^{2} = 1 \). --- To solve \( (x - 8)^{2} = 1 \), take the square root of both sides: \( x - 8 = 1 \) or \( x - 8 = -1 \). Thus, solving for \( x \) gives: 1. \( x = 9 \) 2. \( x = 7 \) So the solutions are \( 9, 7 \).